Use of androgen deprivation therapy as salvage treatment after primary therapy for clinically localized prostate cancer - Fu, Alex Z. (World J Urol, 2016)
PURPOSE: The optimal use of androgen deprivation therapy as salvage treatment (sADT) for men after initial prostatectomy or radiotherapy for clinically localized prostate cancer is undefined. We describe patterns of sADT use and investigate clinical and sociodemographic characteristics of insured men who received sADT versus surveillance in managed care settings. METHODS: Using comprehensive electronic health records and cancer registry data from three integrated health plans, we identified all men with newly diagnosed clinically localized prostate cancer between 1995 and 2009 who received either prostatectomy (n = 16,445) or radiotherapy (n = 19,531) as their primary therapy. We defined sADT based on the timing of ADT following primary therapy and stage of cancer. We fit Cox proportional hazard models to identify sociodemographic characteristics and clinical factors associated with sADT. RESULTS: With a median follow-up of 6 years (range 2–15 years), 13 % of men who underwent primary prostatectomy or radiotherapy received sADT. After adjusting for selected covariates, sADT was more likely to be used in men who were older (e.g., HR 1.70, 95 % CI 1.48–1.96 or HR 1.33, 95 % CI 1.17–1.52 for age 70+ relative to age 35–59 for primary prostatectomy or radiotherapy, respectively), were African-American, had a short PSA doubling time, had a higher pre-treatment risk of progression, had more comorbidities, and received adjuvant ADT for initial disease. CONCLUSIONS: In men with localized prostate cancer in community practice initially treated with prostatectomy or radiotherapy, sADT after primary treatment was more frequent for men at greater risk of death from prostate cancer, consistent with practice guidelines.